Deliberate self-poisoning and suicidality: A qualitative analysis of the factors that influence repetitive suicidal behavior - Kelečević Igor M.; Vejnović Ana-Marija T.; Mijatović-Jovin Vesna M. (Hospital Pharmacology)
Suicide attempts are more common than suicide completions and occur more frequently in women than in men. Patients who survive a suicide attempt are at an increased risk of suicide completion. The most common method of non-lethal suicide attempt is deliberate self-poisoning. Suicidal individuals often have psychiatric comorbidities, most frequently mental and behavioral disorders due to psychoactive substance use and personality disorders. Chronic diseases are also factors that can lead to suicide attempts. Repetitive suicidal behavior is influenced by several important risk factors. Among them, the most important ones are the number of self-harm episodes and the age of suicidal individuals. Other risk factors include male gender, solitary living, and higher social and economic status. Recent studies point to the fact that rates of deliberate self-intoxications are rising among young people and adolescents. The choice of substance for a suicidal act highly depends on its availability. The drugs of choice are usually benzodiazepines, antidepres-sants, antipsychotics, and antiepileptic drugs. However, deliberate self-harm by poisoning sometimes includes illicit drugs. Novel psychoactive substances are a new trend associated with attempted suicides. Survival after deliberate ingestion of substances is common. Hence, it is important to identify individuals at high risk of suicide and work on adequate measures of secondary prevention, while the follow-up period should be long enough in order to reduce the rates of successful suicide following the first episode of suicide attempt by self-poisoning. Health care professionals, family, and society should play an important role in suicide prevention activities.